ALİVE STAY WITH THE CIVILIZATION OF THE QURAN - Halit BOZ (Fırat University, 2019)
Problems in today's world, where people live, a kind of problems can not be resolved by opinion leaders are said to be imposed by the chief civilizations müsebbibinin. Everysociety, a nation, ornations, they produce for their own interests the principles, provisions, conditionsor moral arguments, put forward as a civilization, is not itselfused as a tool forex ploiting nations. Throughout human history, this theory shows that on several occasions in the history to the present day self. Hittite, Sumerian, Persian, Chinese, Roman, Western civilization, the most beautiful example of the above situation in which we are subject. However, untileternity inzalinden Ku'ran present stoman kind civilization, order, and recommended principles, unlike other civilizations who created everything, thesource of "absolutepower" from having produced a civilization that produced by the people for the problems, difficulties, its application in the field of tyranny will never be seen. Goal of this study, thecause of the problem sfaced by Muslims in pörsüyen when they were away from civilization proof of the Qur'an will be a short reviewfor. At thesame time the Qur'an was presented to the humanity civilization, rights and justice, happiness and beauty will be the highlight. The only requirement for Muslims to remain alive mayalarına accordance with their self-released several examples of the Qur'an is their countenan cecivilization, a sense of a we that it is one of the cornerstones of his findings will be brought forward. Thus, the Muslim community, zikrullah kept alive as long as theawe-hinsithatadds life to life again find themselves with in the borders of the vast civilization, never driven, and systems will not match their own Self to flow away.